D09 Parallel evaluation of mutant huntingtin and neurofilament light as biomarkers for huntington's disease: the hd-csf study. (September 2018) - Byrne, Lauren M; Rodrigues, Filipe B; Johnson, Eileanoir B; Wijeratne, Peter A; Vita, Enrico De; Alexander, Daniel C; Czech, Christian; Schobel, Scott; Scahill, Rachael I; Heslegrave, Amanda; Zetterberg, Henrik; Wild, Edward J
Abstract : Background: Huntington's disease (HD) is a progressive neurodegenerative disorder where there is a pressing need for sensitive biomarkers. Aims: We assessed mutant huntingtin (mHTT) and neurofilament light (NfL) in parallel. Methods: CSF mHTT, CSF NfL and plasma NfL were measured using immunoassays in 80 participants (20 healthy controls, 20 premanifest HD and 40 manifest HD) underwent clinical assessments, and standardized CSF and blood collections. Analysis included multiple linear regression models, Pearson's correlations, receiver operating characteristics curves and samples sizes calculations. An event-based model was used to assess the temporal sequence of HD-related biomarker alterations. Results: CSF mHTT, CSF NfL and plasma NfL were significantly higher as disease progressed and associated with all clinical measures. Both CSF and plasma NfL were associated with brain volume measures, but CSF mHTT was not. CSF mHTT, CSF NfL and plasma NfL were closely correlated, and highly stable within individuals. CSF mHTT had perfect accuracy for distinguishing between controls and HD mutation carriers, and both CSF and plasma NfL had excellent accuracy for distinguishing between premanifest and manifest HD. Sample size calculations suggest low participant numbers needed to incorporate these measures into clinical trials. The biofluid biomarkers emerged as the earliest detectable alterations in HD, followed by brain volume, motor and cognitive measures. Conclusion: In this cross-sectional study we provide evidence to support mHTT and NfL as having favourable properties as biofluid biomarkers for HD. Our data suggests that these key biofluid biomarkers are some of the earliest detectable changes in HD.